Endothelial barrier dysfunction in systemic inflammation is mediated by soluble VE-cadherin interfering VE-PTP signaling - Juna-Lisa Knop; Natalie Burkard; Mahshid Danesh; Sebastian Kintrup; Thomas Dandekar; Mugdha Srivastava; Rebecca Springer; Matthias Hiermaier; Nana-Maria Wagner; Jens Waschke; Sven Flemming; Nicolas Schlegel (iScience, 2023)
Summary: Breakdown of endothelial barrier integrity determines organ dysfunction and outcome of patients with sepsis. Increased levels of soluble vascular endothelial (VE)-cadherin fragments (sVE-cadherin) have previously been linked with inflammation-induced loss of endothelial barrier function. We provide evidence for a causative role of sVE-cadherin to induce loss of endothelial barrier function. In patients with sepsis, sVE-cadherin levels were associated with organ dysfunction and the need for volume resuscitation. Similarly, LPS-induced systemic inflammation in rats with microvascular dysfunction was paralleled by augmented sVE-cadherin levels. Newly generated recombinant human sVE-cadherin (extracellular domains EC1-5) induced loss of endothelial barrier function in both human microvascular endothelial cells in vitro and in rat mesenteric microvessels in vivo and reduced microcirculatory flow. sVE-cadherinEC1-5 disturbed VE-cadherin-mediated adhesion and perturbed VE-protein tyrosine phosphatase (VE-PTP)/VE-cadherin interaction resulting in RhoGEF1-mediated RhoA activation. VE-PTP inhibitor AKB9778 and Rho-kinase inhibitor Y27632 blunted all sVE-cadherinEC1-5-induced effects, which uncovers a pathophysiological role of sVE-cadherin via dysbalanced VE-PTP/RhoA signaling.